Emerging illegal wildlife trade issues: A global horizon scan. Issue 4 (23rd April 2020) - Esmail, Nafeesa; Wintle, Bonnie C.; t Sas‐Rolfes, Michael; Athanas, Andrea; Beale, Colin M.; Bending, Zara; Dai, Ran; Fabinyi, Michael; Gluszek, Sarah; Haenlein, Cathy; Harrington, Lauren A.; Hinsley, Amy; et al.
Abstract: Illegal wildlife trade is gaining prominence as a threat to biodiversity, but addressing it remains challenging. To help inform proactive policy responses in the face of uncertainty, in 2018 we conducted a horizon scan of significant emerging issues. We built upon existing iterative horizon scanning methods, using an open and global participatory approach to evaluate and rank issues from a diverse range of sources. Prioritized issues related to three themes: developments in biological, information, and financial technologies; changing trends in demand and information; and socioeconomic, geopolitical shifts and influences. The issues covered areas ranging from changing demographic and economic factors to innovations in technology and communications that affect illegal wildlife trade markets globally; the top three issues related to China, illustrating its vital role in tackling emerging threats. This analysis can support national governments, international bodies, researchers, and nongovernmental organizations as they develop strategies for addressing the illegal wildlife trade.